Value chain upgrading and the inclusion of smallholders in markets: Reflections on contributions of multi-stakeholder processes in dairy development in Tanzania - Kilelu, C.; Klerkx, Laurens; Omore, Amos O.; Baltenweck, Isabelle; Leeuwis, Cees; Githinji, Julius (Springer, 2017)
Increasingly, value chain approaches are integrated with multi-stakeholder processes to facilitate inclusive innovation and value chain upgrading of smallholders. This pathway to smallholder integration into agri-food markets has received limited analysis. This article analyses this integration through a case study of an ongoing smallholder dairy development programme in Tanzania. Value chain upgrading and innovation systems perspectives were combined in an analytical framework to interpret the findings, which show that multi-stakeholder processes enhance horizontal and vertical coordination but limit process and product upgrading. The main conclusion is that, although such processes may catalyze smallholder market inclusion, their effects are largely bounded by existing value chain structures (e.g. production system, fragmented markets), timeframe and how prevailing institutional constraints are addressed, which may constrain the intentions of such collaboration action. This calls attention to the starting points of value chain interventions and the socio-political dynamics that are part of multi-stakeholder processes.